Functional aqueous zinc ion battery electrolyte and preparation method and application thereof
By adding zinc-rich hydroxyl-group-rich polysaccharide additives to the electrolyte of an aqueous zinc-ion battery, adjusting the solvation structure and reducing side reactions, the problem of insufficient cyclic stability of the zinc anode is solved, and the circulation performance and service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202510010511.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The cycle stability of zinc metal anode in aqueous zinc ion batteries is insufficient, mainly due to uneven growth of zinc dendrites and water-induced side reactions, resulting in a short cycle life of the battery.
By introducing zinc-rich hydroxyl-group-rich polysaccharide additives, such as stevia, rohan syringe, etc. into the electrolyte, the solvated structure is adjusted by directed reconstruction of the hydrogen bond network to reduce zinc dendrites' growth and side reactions.
The cycling performance of aqueous zinc ion batteries is significantly improved, the service life of the battery is extended, and the zinc anode is stabilized by preferential adsorption of Zn anode and the growth of zinc dendrites is inhibited.
Smart Images

Figure CN119812511A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a functional aqueous zinc ion battery electrolyte and a preparation method and application thereof. Background Art
[0002] As people pay more and more attention to environmental safety, it is imperative to develop safe, stable, low-cost, high energy density and long cycle stability energy storage devices. -1 and 5851mAhcm -3 ), low redox potential (-0.76 V vs SHE), high earth abundance, and high safety, aqueous zinc-ion batteries (AZIBs) are emerging as a strong contender for next-generation energy storage devices. However, despite the excellent performance of zinc metal anodes in many aspects, their insufficient cycling stability poses a challenge to the practical application of AZIBs.
[0003] These challenges stem from two main aspects: First, the intrinsic Zn dendrite growth, which is rooted in the rapid but unbalanced deposition kinetics, leads to the 2+ The second is water-induced parasitic side reactions, which include hydrogen evolution (HER), Zn metal corrosion, and the formation of electrochemically inert byproducts (Zn4SO4(OH)6·xH2O, i.e., zinc hydroxide). 2+ The uneven deposition of Zn induces the “tip effect”, which eventually causes severe Zn dendrites to penetrate the separator and cause short circuits. These problems severely limit the cycle life of AZIBs. Therefore, it is urgent to design dendrite-free Zn anodes and achieve long-life AZIBs.
[0004] In order to solve the above problems, many methods have been proposed to improve the reversibility of zinc anode, including: Zn anode interface modification, Zn anode structural engineering and electrolyte modification (electrolyte additives). The first two strategies are based on the design of zinc negative electrode. However, the reversibility of zinc anode is still limited due to the uncontrolled side reactions caused by water. Therefore, considering the reliability and effectiveness, electrolyte modification is considered to be a practical method for designing dendrite-free and long-life zinc anodes. At present, the commonly used electrolyte modification method is the use of electrolyte additives. Functional additives can improve the reversibility of zinc anode by providing abundant nucleation sites, changing the Zn 2+ Methods such as ion solvation structure and electrostatic shielding to improve Zn 2+ The plating / stripping ability of ions is to increase the Zn 2+ Ion reversibility. Therefore, exploring functional electrolytes has broad prospects. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a functional aqueous zinc ion battery electrolyte and a preparation method and application thereof, by introducing metal cations (Zn 2+ ) A polysaccharide additive with affinity and rich in zinc-affinity hydroxyl groups. The polysaccharide additive adjusts the solvation structure through the directional reconstruction of the hydrogen bond network, alleviates the hydrogen evolution corrosion reaction of the zinc metal anode in the aqueous zinc ion battery, significantly reduces the corrosion and by-product formation on the surface of the zinc metal anode, significantly improves the cycle performance of the aqueous zinc ion battery, and extends the service life of the aqueous zinc ion battery.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A functional aqueous zinc ion battery electrolyte, comprising a soluble zinc salt, an electrolyte additive and deionized water; the electrolyte additive is one or more of stevioside, mogroside, glycyrrhizin, lactitol, raffinose, stachyose and thaumatin;
[0008] The soluble zinc salt is one of zinc sulfate and zinc trifluoromethanesulfonate.
[0009] Preferably, the concentration of zinc sulfate is 0.5 mol L -1 ~2mol L -1 , preferably 2 mol L -1 The concentration of stevioside is 0.1-0.5 mmol L -1 , preferably 0.3 mmol L -1 The concentration of mogroside is 0.1-0.5 mmol L -1 , preferably 0.3 mmol L -1 ; The concentration of glycyrrhizin is 0.1~0.5mmol L -1 , preferably 0.3 mmol L -1 ; The concentration of lactitol is 0.1~0.5mmol L -1 , preferably 0.3 mmol L -1 ; The concentration of the raffinose is 0.1 to 0.5 mmol L -1 , preferably 0.3 mmol L -1 The concentration of stachyose is 0.1-0.5 mmol L -1 , preferably 0.3 mmol L -1 The concentration of sweet protein is 0.1~0.5mmol L -1 , preferably 0.3 mmol L -1; The mass ratio of the electrolyte additive to deionized water is 0.002g:20g.
[0010] The present invention also provides a method for preparing a functional aqueous zinc ion battery electrolyte, using deionized water to prepare 2 mol L -1 concentration of zinc sulfate electrolyte and add stevia and mix until completely dissolved.
[0011] Preferably, 2 mol L -1 concentration of zinc sulfate electrolyte, and add mogroside and mix until completely dissolved.
[0012] Preferably, 2 mol L -1 Concentration of zinc sulfate electrolyte, add glycyrrhizin and mix until completely dissolved.
[0013] Preferably, 2 mol L -1 Concentration of zinc sulfate electrolyte, and add lactitol and mix until completely dissolved.
[0014] Preferably, 2 mol L -1 Concentration of zinc sulfate electrolyte, and add cottonseed sugar and mix until completely dissolved.
[0015] Preferably, 2 mol L -1 Concentration of zinc sulfate electrolyte, and add stachyose and mix until completely dissolved.
[0016] Preferably, 2 mol L -1 Concentration of zinc sulfate electrolyte, and add sweet protein and mix until completely dissolved.
[0017] The present invention also provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the battery electrolyte obtained by the above-mentioned preparation method.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The edible coloring additives used in the present invention are stevioside, mogroside, glycyrrhizin, lactitol, raffinose, stachyose and sweet protein (thaumatin), which benefit from the polyhydroxy and Zn in the electrolyte additives. 2+ The strong affinity between them reconstructs the hydrogen bond network in the electrolyte and adjusts the solvent structure, effectively reducing the activity of the original H2O molecules. These effects synergistically inhibit dendrite growth, side reactions and corrosion, significantly improve the cycle performance of aqueous zinc-ion batteries, and extend the service life of aqueous zinc-ion batteries.
[0020] 2. The present invention preferentially adsorbs the Zn anode through zinc-philic groups (-COOH, -OH-) to establish a dynamic interface to stabilize the Zn anode, inhibit the growth of zinc dendrites at the zinc negative electrode, thereby improving the charge and discharge cycle stability of the zinc negative electrode and achieving a high-stability zinc anode.
[0021] 3. The raw materials used in the present invention are safe, environmentally friendly, and non-toxic, and the process is simple and easy, highly controllable, low in cost, and has strong industrial applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 1 of the present invention;
[0023] Figure 2 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 2 of the present invention;
[0024] Figure 3 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 3 of the present invention;
[0025] Figure 4 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 4 of the present invention;
[0026] Figure 5 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 5 of the present invention;
[0027] Figure 6 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 6 of the present invention;
[0028] Figure 7 The cycle performance diagram of the aqueous zinc ion battery assembled with the electrolyte of Example 7 of the present invention;
[0029] Figure 8 This is a scanning electron microscope image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 8 of the present invention after cycling;
[0030] Fig. 9 This is a scanning electron microscope image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 9 of the present invention after cycling;
[0031] Fig.10 This is a scanning electron microscope image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 10 of the present invention after cycling;
[0032] Fig.11 This is a scanning electron microscopy image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 11 of the present invention after cycling;
[0033] Fig.12This is a scanning electron microscope image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 12 of the present invention after cycling;
[0034] Fig.13 Scanning electron microscope image of the zinc negative electrode of the aqueous zinc ion battery assembled with the electrolyte of Example 13 of the present invention after cycling;
[0035] Fig.14 This is a scanning electron microscope image of the zinc negative electrode of an aqueous zinc ion battery assembled with the electrolyte of Example 14 of the present invention after cycling;
[0036] Fig.15 This is a cycle performance diagram of an aqueous zinc ion battery assembled with the electrolyte of Comparative Example 1 of the present invention;
[0037] Fig.16 This is a scanning electron microscope image of the zinc negative electrode of the aqueous zinc ion battery assembled with the electrolyte of Comparative Example 2 of the present invention after cycling. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0039] The experimental methods in the following examples without specifying specific conditions are usually carried out according to conventional conditions or conditions recommended by the manufacturer.
[0040] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment, and the purity was analytically pure. Stevioside, mogroside, glycyrrhizin, lactitol, raffinose, stachyose and sweet protein (thaumatin) were purchased from Aladdin Reagent Company with a molecular weight of 100-1500.
[0041] The testing and analysis instruments used in the examples of this application are as follows:
[0042] A constant current charge and discharge test was performed using a battery tester (CT-4008Tn-5V10mA) from Xinwei Electronics.
[0043] Example 1
[0044] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn symmetric battery with stevia as the electrolyte was tested.
[0045] (1) Prepare electrolyte
[0046] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 24.5 mg of stevioside in the above ZnSO4 solution to make 2 mol L -1 ZnSO4+0.3mmol L -1 Stevia electrolyte.
[0047] (2) Preparation of electrodes
[0048] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0049] (3) Symmetrical battery assembly
[0050] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Stevia solution is used as electrolyte, and a button-type CR2032 symmetrical battery is assembled in the order of a negative electrode shell, a shrapnel, a gasket, a zinc foil, a diaphragm, a zinc foil and a positive electrode shell.
[0051] (4) Symmetrical battery performance test
[0052] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0053] The battery performance test results are as follows: Figure 1 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with stevia electrolyte achieved a long cycle life of 275h.
[0054] Example 2
[0055] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 Battery testing was performed on a Zn||Zn symmetric battery with mogroside as the electrolyte.
[0056] (1) Prepare electrolyte
[0057] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 43.5 mg of mogroside in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Mogroside electrolyte.
[0058] (2) Preparation of electrodes
[0059] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0060] (3) Symmetrical battery assembly
[0061] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The mogroside solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0062] (4) Symmetrical battery performance test
[0063] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0064] The battery performance test results are as follows: Figure 2 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with mogroside electrolyte achieved a long cycle life of 1630h.
[0065] Example 3
[0066] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 Battery testing was performed on a Zn||Zn symmetric battery with glycyrrhizin as the electrolyte.
[0067] (1) Prepare electrolyte
[0068] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 24.6 mg of glycyrrhizin in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Licorice electrolyte.
[0069] (2) Preparation of electrodes
[0070] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0071] (3) Symmetrical battery assembly
[0072] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The glycyrrhizin solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0073] (4) Symmetrical battery performance test
[0074] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0075] The battery performance test results are as follows: Figure 3 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with glycyrrhizin electrolyte achieved a long cycle life of 308h.
[0076] Example 4
[0077] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 Battery testing was performed on a Zn||Zn symmetric battery with lactitol as the electrolyte.
[0078] (1) Prepare electrolyte
[0079] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 10.3 mg of lactitol in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Lactitol electrolyte.
[0080] (2) Preparation of electrodes
[0081] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0082] (3) Symmetrical battery assembly
[0083] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Lactitol solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0084] (4) Symmetrical battery performance test
[0085] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0086] The battery performance test results are as follows: Figure 4 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with lactitol electrolyte achieved a long cycle life of 831 h.
[0087] Example 5
[0088] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 Battery testing was performed on a Zn||Zn symmetric battery with cottonseed sugar as the electrolyte.
[0089] (1) Prepare electrolyte
[0090] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 15.1 mg of raffinose in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Raffinose electrolyte.
[0091] (2) Preparation of electrodes
[0092] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0093] (3) Symmetrical battery assembly
[0094] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Raffinose solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a shrapnel, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0095] (4) Symmetrical battery performance test
[0096] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0097] The battery performance test results are as follows: Figure 5 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with cottonseed sugar electrolyte achieved a long cycle life of 360 h.
[0098] Example 6
[0099] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn symmetric battery with stachyose as the electrolyte was tested.
[0100] (1) Prepare electrolyte
[0101] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 19.9 mg of stachyose in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Stachyose electrolyte.
[0102] (2) Preparation of electrodes
[0103] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0104] (3) Symmetrical battery assembly
[0105] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Stachyose solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0106] (4) Symmetrical battery performance test
[0107] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0108] The battery performance test results are as follows: Figure 6 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with stachyose electrolyte achieved a long cycle life of 322 h.
[0109] Example 7
[0110] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 Battery testing was performed on a Zn||Zn symmetric battery with sweet protein as the electrolyte.
[0111] (1) Prepare electrolyte
[0112] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 20.1 mg of sweet protein in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Sweet protein electrolyte.
[0113] (2) Preparation of electrodes
[0114] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0115] (3) Symmetrical battery assembly
[0116] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The sweet protein solution is used as the electrolyte, and a button-type CR2032 symmetrical battery is assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0117] (4) Symmetrical battery performance test
[0118] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0119] The battery performance test results are as follows: Figure 7 At 5 mA cm -2 Current density (area capacity 1mAh·cm -2 ), using 2 mol L -1 ZnSO4+0.3mmol L -1 The Zn||Zn battery with sweet protein electrolyte achieved a long cycle life of 192h.
[0120] Example 8
[0121] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetrical battery with stevia as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0122] (1) Prepare electrolyte
[0123] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 24.5 mg of stevioside in the above ZnSO4 solution to make 2 mol L -1 ZnSO4+0.3mmol L -1 Stevia electrolyte.
[0124] (2) Preparation of electrodes
[0125] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0126] (3) Symmetrical battery assembly
[0127] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Stevia solution is used as electrolyte, and a button-type CR2032 symmetrical battery is assembled in the order of a negative electrode shell, a shrapnel, a gasket, a zinc foil, a diaphragm, a zinc foil and a positive electrode shell.
[0128] (4) Symmetrical battery performance test
[0129] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0130] (5) Electrode cleaning and electron microscope testing
[0131] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0132] The electron microscopy results are as follows Figure 8 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0133] Example 9
[0134] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetrical battery with mogroside as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0135] (1) Prepare electrolyte
[0136] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 43.5 mg of mogroside in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Mogroside electrolyte.
[0137] (2) Preparation of electrodes
[0138] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0139] (3) Symmetrical battery assembly
[0140] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The mogroside solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0141] (4) Symmetrical battery performance test
[0142] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0143] (5) Electrode cleaning and electron microscope testing
[0144] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0145] The electron microscopy results are as follows Fig. 9 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0146] Example 10
[0147] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetrical battery with glycyrrhizin as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0148] (1) Prepare electrolyte
[0149] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 24.6 mg of glycyrrhizin in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Licorice electrolyte.
[0150] (2) Preparation of electrodes
[0151] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0152] (3) Symmetrical battery assembly
[0153] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The glycyrrhizin solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0154] (4) Symmetrical battery performance test
[0155] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0156] (5) Electrode cleaning and electron microscope testing
[0157] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0158] The electron microscopy results are as follows Fig.10 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0159] Embodiment 11
[0160] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetrical battery with lactitol as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0161] (1) Prepare electrolyte
[0162] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, then dissolve 10.3 mg of lactitol in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Lactitol electrolyte.
[0163] (2) Preparation of electrodes
[0164] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0165] (3) Symmetrical battery assembly
[0166] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Lactitol solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0167] (4) Symmetrical battery performance test
[0168] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0169] (5) Electrode cleaning and electron microscope testing
[0170] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0171] The electron microscopy results are as follows Fig.11 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0172] Example 12
[0173] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetric battery with cottonseed sugar as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0174] (1) Prepare electrolyte
[0175] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 15.1 mg of raffinose in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Raffinose electrolyte.
[0176] (2) Preparation of electrodes
[0177] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0178] (3) Symmetrical battery assembly
[0179] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Raffinose solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a shrapnel, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0180] (4) Symmetrical battery performance test
[0181] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0182] (5) Electrode cleaning and electron microscope testing
[0183] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0184] The electron microscopy results are as follows Fig.12 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0185] Embodiment 13
[0186] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1 A Zn||Zn symmetric battery with stachyose as the electrolyte was subjected to a battery cycle test, and the electrode pieces obtained after the test were subjected to a scanning electron microscope test.
[0187] (1) Prepare electrolyte
[0188] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 19.9 mg of stachyose in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Stachyose electrolyte.
[0189] (2) Preparation of electrodes
[0190] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0191] (3) Symmetrical battery assembly
[0192] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 Stachyose solution was used as electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0193] (4) Symmetrical battery performance test
[0194] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0195] (5) Electrode cleaning and electron microscope testing
[0196] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0197] The electron microscopy results are as follows Fig.13 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0198] Embodiment 14
[0199] Assemble 2 mol L -1 ZnSO4+0.3mmol L -1A Zn||Zn symmetric battery with sweet protein as the electrolyte was subjected to battery cycle test, and the electrode pieces obtained after the test were subjected to scanning electron microscope test.
[0200] (1) Prepare electrolyte
[0201] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution, and then dissolve 19.9 mg of sweet protein in the above ZnSO4 solution to prepare 2 mol L -1 ZnSO4+0.3mmol L -1 Sweet protein electrolyte.
[0202] (2) Preparation of electrodes
[0203] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0204] (3) Symmetrical battery assembly
[0205] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4+0.3mmol L -1 The sweet protein solution is used as the electrolyte, and a button-type CR2032 symmetrical battery is assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0206] (4) Symmetrical battery performance test
[0207] Normal temperature cycle performance test, set the charge and discharge current to 1mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0208] (5) Electrode cleaning and electron microscope testing
[0209] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0210] The electron microscopy results are as follows Fig.14 As shown, the surface of the zinc sheet is flat and uniform, showing a dense surface without obvious dendrite formation.
[0211] Comparative Example 1
[0212] Assemble 2 mol L -1A Zn||Zn symmetrical battery with ZnSO4 as the electrolyte was used for battery testing.
[0213] (1) Prepare electrolyte
[0214] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution.
[0215] (2) Preparation of electrodes
[0216] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0217] (3) Symmetrical battery assembly
[0218] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4 solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0219] (4) Symmetrical battery performance test
[0220] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Long cycle performance test was carried out under the following conditions.
[0221] The battery performance test results are as follows: Fig.15 As shown. At 5mAcm -2 Current density (area capacity 1mAh m -2 ), using 2 mol L -1 The Zn||Zn battery with ZnSO4 electrolyte achieved a cycle life of 38h.
[0222] Comparative Example 2
[0223] Assemble 2 mol L -1 Zn||Zn symmetric battery with ZnSO4 as electrolyte, subjected to electron microscopy test.
[0224] (1) Prepare electrolyte
[0225] Weigh 32g of zinc sulfate and dissolve it in 100mL of deionized water to make 2mol L -1 ZnSO4 solution.
[0226] (2) Preparation of electrodes
[0227] The surface of the zinc foil with a thickness of 100 μm was polished to be smooth with 600 mesh, 800 mesh and 2000 mesh sandpaper in sequence, cut into discs with a diameter of 16 mm, ultrasonically rinsed with ethanol-free and deionized water for 15 minutes, rinsed clean, and vacuum dried.
[0228] (3) Symmetrical battery assembly
[0229] Two Zn sheets were used as the positive and negative electrodes of the battery, respectively, and a glass fiber filter membrane was used as the diaphragm. -1 ZnSO4 solution was used as the electrolyte, and a button-type CR2032 symmetrical battery was assembled in the order of a negative electrode shell, a spring, a gasket, a zinc foil, a separator, a zinc foil and a positive electrode shell.
[0230] (4) Symmetrical battery performance test
[0231] Normal temperature cycle performance test, set the charge and discharge current to 5mAcm at 25℃ -2 , fixed charge and discharge capacity is 1mAcm -2 Cycle 20 times under the same conditions.
[0232] (5) Electrode cleaning and electron microscope testing
[0233] The cycled battery was disassembled and cleaned three times with deionized water and anhydrous ethanol alternately. The dendrite growth on the zinc electrode surface was observed using a scanning electron microscope.
[0234] The electron microscopy results are as follows Fig.16 As shown, there are many flake-like dendrites on the surface of the zinc sheet.
[0235] In summary, the present invention uses a polysaccharide additive containing multiple hydroxyl groups as an additive for zinc ion batteries, which can utilize the hydroxyl groups to react with Zn 2+ The strong affinity between Zn and polysaccharides can be achieved by regulating the solvation structure through the directional reconstruction of the hydrogen bond network. In addition, the polysaccharide additives are preferentially adsorbed on the Zn anode surface to form a local water-poor interface, reducing unnecessary side reactions caused by water, thereby establishing a stable Zn anode.
[0236] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A functional aqueous zinc ion battery electrolyte, characterized in that: The invention comprises a soluble zinc salt, an electrolyte additive and deionized water; the electrolyte additive is one or more of stevioside, mogroside, glycyrrhizin, lactitol, raffinose, stachyose and sweet protein; The soluble zinc salt is one of zinc sulfate and zinc trifluoromethanesulfonate.
2. A functional aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of zinc sulfate is 0.5 mol L -1 ~2mol L -1 The concentration of stevioside is 0.1-0.5 mmol L -1 The concentration of mogroside is 0.1-0.5 mmol L -1 The concentration of glycyrrhizin is 0.1-0.5 mmol L -1 The concentration of lactitol is 0.1 to 0.5 mmol L -1 The concentration of raffinose is 0.1-0.5 mmol L -1 The concentration of stachyose is 0.1-0.5 mmol L -1 The concentration of sweet protein is 0.1 to 0.5 mmol L -1 The mass ratio of the electrolyte additive to deionized water is 0.002g:20g.
3. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 concentration of zinc sulfate electrolyte and add stevia and mix until completely dissolved.
4. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 concentration of zinc sulfate electrolyte, and add mogroside and mix until completely dissolved.
5. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 Concentration of zinc sulfate electrolyte, add glycyrrhizin and mix until completely dissolved.
6. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 Concentration of zinc sulfate electrolyte, and add lactitol and mix until completely dissolved.
7. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 Concentration of zinc sulfate electrolyte, and add cottonseed sugar and mix until completely dissolved.
8. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 Concentration of zinc sulfate electrolyte, and add stachyose and mix until completely dissolved.
9. The method for preparing a functional aqueous zinc ion battery electrolyte according to claim 2, characterized in that: Use deionized water to prepare 2 mol L -1 Concentration of zinc sulfate electrolyte, and add sweet protein and mix until completely dissolved.
10. An aqueous zinc ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is a battery electrolyte obtained by the preparation method according to any one of claims 3 to 9.
Citation Information
Cited By
Zinc ion battery electrolyte containing polysaccharide zinc chelate as well as preparation method and application of zinc ion battery electrolyte
CN120221824A